2010
DOI: 10.1186/1746-4269-6-24
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoveterinary plant remedies used by Nu people in NW Yunnan of China

Abstract: BackgroundNu people are the least populous ethnic group in Yunnan Province of China and most are distributed in Gongshan County, NW Yunnan. Animal production plays an important role in Nu livelihoods and the Nu people have abundant traditional knowledge of animal management and ethnoveterinary practices. This study documents the animal diseases, ethnoveterinary plant remedies and related traditional knowledge in three Nu villages of Gongshan County.MethodsThis study was carried out in three Nu villages of Gong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 19 publications
10
48
1
2
Order By: Relevance
“…These rout of administrations, both oral and topical routes, they considered rapid physiological reaction with the causative agents and increase the curative power of the medicinal plant remedies. This observation was coincided with the findings of study in Nu villages of China, [33] Jimma zone [30] and Gimbi district, West Wellega, [34] Ethiopia. In addition to this, the herbalists applied the remedies sediments on the external body of the sick animal.…”
Section: Resultssupporting
confidence: 58%
“…These rout of administrations, both oral and topical routes, they considered rapid physiological reaction with the causative agents and increase the curative power of the medicinal plant remedies. This observation was coincided with the findings of study in Nu villages of China, [33] Jimma zone [30] and Gimbi district, West Wellega, [34] Ethiopia. In addition to this, the herbalists applied the remedies sediments on the external body of the sick animal.…”
Section: Resultssupporting
confidence: 58%
“…Community based validation exercise lends credibility and reinforce location specific knowledge systems. This is in concurrence with Shen et al (2010) who opined that IKRS can minimize input cost for small holder farming system. This approach may enhance rate of adoption of socially acceptable medications in control of livestock ailments (Raot et al, 2016).…”
Section: How To Access Alternative Technology When Package Of Practicsupporting
confidence: 59%
“…Clearly, livestock farmers in this study held general rather than specialized ethno-veterinary knowledge. The study of Shen et al (2010) carried out among the Nu pastoralists in North West China concluded that there were no publicly recognized specialists. Knowledge was derived from daily practice of livestock production although it does not mean that there are no ethno-veterinary specialists.…”
Section: Discussionmentioning
confidence: 99%